Deep fluids migration and submarine emersion of the Kalang Anyar mud volcano (Java, Indonesia): A multidisciplinary study. (February 2023) - Mazzini, Adriano; Sciarra, Alessandra; Lupi, Matteo; Ascough, Philippa; Akhmanov, Grigorii; Karyono, Karyono; Husein, Alwi
Abstract: North-east Java is part of a large sedimentary basin containing hydrocarbon provinces that feature diffuse hydrothermal systems, mud volcanoes, and degassing sites. Seismic profiles acquired to explore the basin reveal a broad distribution of palaeo- and modern piercement structures. The Watukosek fault system links the volcanic arc, to the south, with the Sidoarjo province, to the north. Several piercement structures, including the Kalang Anyar mud volcano, are hosted along this left-lateral strike-slip system that favors the migration of crustal fluids in this part of the basin. Here, we present a multidisciplinary geological, geophysical and geochemical study conducted at Kalang Anyar where dozens of seepage sites are active in the crater area and intermittently emit bursts oil, gas, mud, and water. The emitted gasses are methane-dominated with smaller amounts of heavier hydrocarbons and CO2 . Unlike most mud volcanoes, at Kalang Anyar the mixed-thermogenic origin of the methane is coupled with geothermal anomalies, as indicated by helium and CO2 isotopic values (δ 13 CCO2 as high as −4‰) that suggest the input of mantle-derived gas. Our gas flux measurements reveal that Kalang Anyar emits about 1.62 and 5.75 t yr −1 of CO2 and CH4, respectively. The intense bubbling gives rise to a typical drumbeat seismic signal characterized by dominant frequencies around of 3–4 Hz (and up to 15 Hz). We interpret the drumbeat as fluids rising and resonating through shallow plumbing system of Kalang Anyar. Erupted clasts with different lithologies and shells are scattered across the mud volcano area, while the edges of the crater zone include cubic meter-sized carbonate-cemented blocks and ridges that contain siliciclastic sediments and abundant chemosymbiotic bivalves. Carbon isotope analyses of the carbonate cement (δ 13 C as low as −48.8‰) identify the latter as methanogenic chemoherms. Radiocarbon ( 14 C) dating of bivalves cemented in the blocks indicates an age of 1890-1488 BP. These results indicate that the activity of Kalang Anyar MV dates from when the area was below sea level and that the microbially-mediated precipitation of carbonates was ongoing during subaqueous methane seepage at the crater site. To the best of our knowledge, Kalang Anyar is the first example of a mud volcano that progressed from subaqueous to subaerial conditions during marine regression, displaying evidence of former marine activity (i.e. methanogenic carbonates) and current subaerial degassing at numerous seepage sites. Potentially eruptive phases represent a clear geohazard for the numerous settlements constructed inside the mud volcano. In light of this, it may be prudent to apply stricter rules for development activities, such as housing construction permits that consider the possibility of potentially catastrophic events, and apply steps to mitigate these hazards. Highlights: Kalang Anyar mud volcano has intense bubbling activity with emergent seismic signal. Dating of methanogenic carbonate blocks reveal previous Holocene offshore vigorous degassing. Activity progressed from subaqueous to subaerial conditions during postglacial sea regression. Geochemistry of seeping fluids indicate deep-sourced mantle-derived component. Tectonic discontinuities promote migration of volcanic fluids and piercements formation.